High-temperature electron microscopy study of ThO2 microspheres sintering. Issue 2 (February 2017) - Nkou Bouala, G.I.; Clavier, N.; Léchelle, J.; Monnier, J.; Ricolleau, Ch.; Dacheux, N.; Podor, R.
Abstract: The behavior of ThO2 microspheres was investigated in situ at high temperature by electron microscopy, including HR-TEM and ESEM. The observation of isolated particles first allowed to describe the mechanisms driving the growth of crystallites within the microspheres, i.e. a combination of oriented attachment and solid-state diffusion, and to evaluate the associated activation energies. Polycrystalline and single-crystal two-grain systems were further investigated to monitor the formation of a neck during heat treatment. For single crystals, the topological evolution was found to agree well with the models, whereas the establishment of neck between two polycrystalline microspheres deviated from the expected trend, with the formation of intermediate large-size crystallites. Such modification was mainly assigned to the microstructures of the particles used, showing that the level of polycrystallinity of the powder and its initial porosity, which both arose from the synthesis method, must be considered carefully to evaluate its sintering capability.